2022
DOI: 10.1101/2022.04.28.489914
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dissecting the phase separation and oligomerization activities of the carboxysome positioning protein McdB

Abstract: Carboxysomes are protein-based organelles essential for efficient CO2-fixation in cyanobacteria and some chemoautotrophic bacteria. We recently identified the two-component system responsible for spatially regulating carboxysomes, consisting of the proteins McdA and McdB. McdA is a member of the ParA/MinD-family of ATPases, which position a variety of cellular cargos across bacteria. McdB, however, represents a widespread but unstudied class of proteins. We previously found that McdB forms a hexamer and underg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 102 publications
(160 reference statements)
2
19
0
Order By: Relevance
“…McdB sol mutant, the net negative charge of its IDR was increased 25 ; therefore, we speculate that the localization pattern of the fluidized PAmCherry-McdB condensate is due to nucleoid exclusion by repulsive electrostatic interactions. Consistently, we found that mCherry-McdB sol foci expanded and encroached throughout the cytoplasm as the nucleoid was compacted via drug treatment (Supplementary Fig.…”
Section: Using Tunable Promoters To Probe the Formation Of Biomolecul...mentioning
confidence: 84%
See 2 more Smart Citations
“…McdB sol mutant, the net negative charge of its IDR was increased 25 ; therefore, we speculate that the localization pattern of the fluidized PAmCherry-McdB condensate is due to nucleoid exclusion by repulsive electrostatic interactions. Consistently, we found that mCherry-McdB sol foci expanded and encroached throughout the cytoplasm as the nucleoid was compacted via drug treatment (Supplementary Fig.…”
Section: Using Tunable Promoters To Probe the Formation Of Biomolecul...mentioning
confidence: 84%
“…Based on the linker lengths, PopTag LL -mCherry condensates should be more fluid than PopTag SL -mCherry condensates, which we expect to be more viscous or in a gel-like state 26 . Additionally, we probed a solubilized McdB mutant (McdB sol ), previously shown to be abrogated in its phase separation activity both in vitro and in vivo 25 . Finally, mCherry alone was used as a control for a completely soluble protein.…”
Section: Using Tunable Promoters To Probe the Formation Of Biomolecul...mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the linker lengths, PopTag LL -mCherry condensates should be more uid than PopTag SL -mCherry condensates, which we expect to be more viscous or in a gel-like state 26 . Additionally, we probed a solubilized McdB mutant (McdB sol ), previously shown to be abrogated in its phase separation activity both in vitro and in vivo 25 . Finally, mCherry alone was used as a control for a completely soluble protein.…”
Section: Using Tunable Promoters To Probe the Formation Of Biomolecul...mentioning
confidence: 99%
“…We developed and adapted a suite of molecular and cell biology methodologies along with super-resolution imaging techniques in Escherichia coli to characterize the formation, solubility, and dynamic exchange of condensates. We examined the protein McdB, a component of the carboxysome positioning system that robustly forms phase-separated droplets in vitro [23][24][25] , alongside well-established control proteins that form condensates 26 and insoluble aggregates 27,28 . First, we qualitatively probed the liquid-like properties of McdB condensates using overexpression assays.…”
mentioning
confidence: 99%